Molecular identification of pathogenic bacteria and PCR specific primer design - Aris, Muh.; Sukenda, Sukenda; Harris, Enang; Sukadi, Muh. Fatuhcri (Universitas Sam Ratulangi, 2013)
Management of healthy seaweed aquaculture and control of ice ice disease are important component in seaweed production. To support the integrated prevention of ice ice disease, information about genetic variation of bacterial pathogen and the availability of fast and accurate detection are required. This study aimed to identify bacterial pathogen based on gene sequence analysis 16S-rRNA, construction of specific PCR primer from gene sequent analysis 16S-rRNA from bacteria that had the highest pathogenicity. Gene 16S rRNA of bacteria that had the highest pathogenicity was amplificated with universal primer PCR domain forward primer 63f (5’-CAG GCC TAA CAC ATG CAA GTC-3’) and reverse primer 1387r (5’-GGG CGG WGT GTA CAA GGC-3’). DNA Sequence obtained was compared to data base European Bioinformatics Institute (EBI) BLASTN. Construction and feasibility analysis of primer pair was done using primer 3 program. Two specific primer PCR were successfully constructed namely aSEFM-F (5- CAGCCACACTGGAACTGAGA-3) and aSEFM-R(5 TTAGCCGGTGCTTCTTCTGT -3). Both primer reacted optimum at 60°C and produced 201 bp amplicon. Keywords: pathogenicity, gene 16S-rRNA, PCR, primer, specific